'The Coming Clash of East and West': syncretism, cosmopolitanism, and disaffection in the colonial public sphere. Issue 4 (7th June 2017) - Agathocleous, Tanya
ABSTRACT: This essay analyses the modernist Indian journal 'East and West', published in Bombay from 1901 to 1921, as a significant instance of how and why syncretic ideals circulated in the colonial public sphere in India. The idea of East–West union, I argue, was a form of modernist cosmopolitanism that mediated between Enlightenment public sphere ideals and an emergent, 'spiritual cosmopolitanism', critical of Western values. It was also a way to conform to the government's criminalisation of the Indian press for expressions of 'disaffection'; by professing its allegianceto East–West friendship, but demonstrating the fallacy of this idea in practice through its juxtaposition of articles by British and Indian writers, the journal gives us insight into the changing valences of cosmopolitanism over the period of its circulation; the way syncretism mediated between these valences; and how these discourses were shaped by the regulation of the press.